2015
DOI: 10.5038/1936-4660.8.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Literacy and Co-Construction in a High School Math Course

Abstract: This article reports some of the key findings from a practitioner-action research study that analyzed the impact of co-construction on students' quantitative literacy (QL) and attitudes towards mathematics. Coconstruction is a process where students work alongside their teachers to plan units, lessons, and assessments, and this approach was chosen because of its potential to help students advocate for the specific mathematical contexts that would best develop their QL. This yearlong study took place in a publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Student participation is necessary in co-construction and thus I created structures and activities for co-construction to occur regularly (Ahlquist, 1991;Evans et al, 2006). Darryl indicated that co-constructing policies invited students to participate in other components of the class (Russo, 2015). I was hoping that co construction would create opportunities for students to participate who normally wouldn't participate, something that was affirmed by Carrie and Juanita (Chen, 2016;Clarke, 2004;Langer-Osuna, 2007;Mueller, 2009;Russo, 2015).…”
Section: Discussion Of Findings Section 1: Privileging Student Voicementioning
confidence: 99%
See 4 more Smart Citations
“…Student participation is necessary in co-construction and thus I created structures and activities for co-construction to occur regularly (Ahlquist, 1991;Evans et al, 2006). Darryl indicated that co-constructing policies invited students to participate in other components of the class (Russo, 2015). I was hoping that co construction would create opportunities for students to participate who normally wouldn't participate, something that was affirmed by Carrie and Juanita (Chen, 2016;Clarke, 2004;Langer-Osuna, 2007;Mueller, 2009;Russo, 2015).…”
Section: Discussion Of Findings Section 1: Privileging Student Voicementioning
confidence: 99%
“…The exceptions are senior level elective courses which can vary by high school. Russo (2015) conducted practitioner action research in his quantitative literacy course for high school seniors who struggled in Algebra. In this elective course, he utilized co-construction to develop the course and had several findings: students and teachers needed time to adjust to a co-constructed classroom and co-construction resulted in increased participation, interest and ownership of learning.…”
Section: Co-constructionmentioning
confidence: 99%
See 3 more Smart Citations